Functional study of a novel SCN4A variant c.611C>T identified in a Japanese patient with myasthenia - Kira, Natsuki; Yoshida, Kosuke; Takahashi, Satoe; Yamanaka, Ayami; Kimura, Takashi; Homma, Kazuaki; Takahashi, Masanori P.; Kubota, Tomoya (Frontiers in Biophysics, 2026)
Recent advances in sequencing technologies have significantly contributed to the identification of disease-associated gene variants. However, a substantial number of patients, particularly those presenting with atypical neuromuscular phenotypes, remain genetically undiagnosed. Herein, we report a case of a Japanese patient with myasthenic symptoms in the eyelids and limbs rather than periodic paralysis having a novel heterozygous variant (c.611C>T) located at the 3′ end of exon 4 in SCN4A. The analysis of the proband’s SCN4A mRNA showed that this variant causes an alanine-to-valine missense change at the amino acid position of 204 (p.A204V, 39%) and a disruption of the splicing of exons 4 and 5 leading to the production of truncated Nav1.4 variant protein (p.A204Vfs*94, 4%). We anticipated that the p.A204V missense change would impair Nav1.4 function; however, the ion channel activity and membrane targeting of p.A204V Nav1.4 were found to be wild-type (WT)-like. We also examined the cytotoxicities of the p.A204V and p.A204Vfs*94 variants; however, the cell lines heterologously overexpressing these Nav1.4 variant proteins did not induce cell death any more than the WT control. Although the loss or gain of anomalous ion channel function that is commonly suspected in channelopathies was ruled out in the present case, the precise mechanism of the pathogenic role of c.611C>T SCN4A remains to be elucidated.